Language learning with copacabana / Sharifah Sheha Syed Aziz Baftim - Syed Aziz Baftim, Sharifah Sheha (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Songs and music in the classroom are known to be attractive and act as a valuable teaching tools in language learning. They can be fully utilized to help students improve on various skills of the language. Thus, an action research in the classroom was developed to allow students to practice on the various language skills through a song. The purpose of this study was to develop activities in the classroom that integrate the four major language skills through the use of a song. Using the song entitled Copacabana by Barry Manilow, this study explored some possible ways in enhancing language learning in all the four major language skills basically grammar, reading, listening and speaking. Through a survey that was carried out, this approach received positive feedbacks from the students. It was observed that students were more responsive and attentive in class when using this approach. Thus, integrating songs into language learning serves not only as an effective teaching tool, but it provides a positive learning experience for students.